The effects of the jejemon phenomenon on the communication skills of six Mati National Comprehensive High School students in the informal context - Oliveros, Lavinia
This study aims to describe the effects of the jejemon phenomenon which is regarded as popular as a popular culture in the Philippines, on the communication skills of six Mati National Comprehensive High School students practice Jejetyping. This study, however, is limited to informal context only. This paper used the qualitative descriptive case study as a research design. To achieve the objectives of this study, the researcher went to Mati National Comprehensive High School and interviewed six students who have been practicing Jejetyping. This study found out that the respondents take considerations on who they are going to text before deciding to use. Jejemon in communicating since they do not use Jejemon to all of their receivers. Aside from their receivers, the respondents also consider what channels and in what situations they use jejemon. In addition, the Jejemon phenomenon has also affected the respondents' expressive skills. Moreover, the use of Jejemon of the five respondents in communicating to people who do not use it exhibits the concept of power in communication. Their knowledge of the Jejemon gives them power over the people who could not understand it. The Jejemon also appeared that it could be a communication barrier as respondents recounted their experiences of misunderstanding with their receivers because of Jejemon